Preferensi Penghuni Terhadap Lingkungan Tempat Tinggal di Rusunawa Marunda, Kecamatan Cilincing Jakarta Utara - Ramadhan, Juniarto; Manaf, Asnawi (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
This research was conducted by the phenomena of Jakarta Regional Government's policy on city planning, which reduces slums by relocating residents in illegal slum areas. The relocation was excellent, resulting in revitalization of illegal slum area while restorating its function as green spaces, water catchment area, and river engineering to reduce annual flood which was an annual disaster in Jakarta. The relocation was executed around Pluit Reservoir, Fish Market, and KaliJodo, where slums were relocated to Rusunawa, a government-subsidized flats in Jakarta. Rusunawa Marunda is one of them.This study aims to determine the resident preferences in occupying Rusunawa Marunda. Points to be analyzed are 1) Physical characteristics of Rusunawa Marunda, 2) Resident characteristics of Rusunawa Marunda, 3) Occupants' preference to stay in Rusunawa Marunda. Characteristic identification of the residents were analysed using mixed method with sequential transformative strategy. Several chosen variables were analyzed using Crosstab analysis to find correlations between indicators. The occupant preference factor were analysed using descriptive analysis of quantitative and analytical weighting (Likert). A comparation between low income occupants (MBR) and the general occupants (non-MBR) shows that the level of preference of these two type of inhabitants are very diverse, as physical quality and settlement in Rusunawa is better and more comfortable than their home before. However, social significant changes on residents do occur after occupying Rusunawa especially in wealth aspects, where new residents who do not have permanent jobs, lack of education and skills are forced to change profession and had to find new source of income. Thus, becoming a major influence in the reduction of family income.